Penerapan Model Problem Solving Untuk Meningkatkan Hasil Belajar Siswa Pada Muatan PKn Kelas II SDN Dinoyo 1 Kota Malang - Chusnul Chotimah; Kardiana Metha Rozhana; Olivia Tanggu Solo (Universitas Muhammadiyah Kuningan, 2024)
The research aims to improve teaching patterns and improve student behavior in improving the practice of teaching and learning processes to gain new knowledge and as the development of knowledge in the scientific field of data collection.The research method used was descriptive qualitative in the form of Classroom Action Research with data collection techniques namely observation, data analysis techniques, and test techniques in Cycle I and Cycle II with 28 students as subjects. This research was conducted at SDN Dinoyo 1 Malang City with the results showing that in the first cycle, the student learning achievement was 78.57% and in the second cycle it increased to 96.42%. This shows that the research results in cycle II have reached indicators of success.From the results of this study, it can be concluded that the use of problem-solving models in the teaching and learning process can improve PKn learning outcomes about Pancasila for class II students at SDN Dinoyo 1 Malang City. Suggestions for teachers to always innovate and design interesting teaching and learning processes, one of the ways is by using the Problem Solving model in the learning process in class. For schools, based on the results of this study, schools are expected to be able to use it as a reference material to develop the quality of the teaching and learning process. It is suggested for further researchers to conduct this research with different subjects, to obtain broader research results and be useful as information material for the world of education.